Risk Production Analysis Rice Farming with Just and Pope Approach - Purnamasari, Fitry; Rosadi, Sri Hardianti; Muliani, Muliani; Ridwan, Wardimansyah (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2024)
Rice plants are included in agricultural commodities that have a high risk. Farming risks can be caused by agroecological environmental factors, input factors and management. This study aims to (1) determine the magnitude of the production risk of rice farming; (2) Identify production factors that affect rice production risks; This research was conducted in Lampulung Village, Pammana District, Wajo Regency. The population in this study amounted to 618 people. From this population, 5% of the population was taken so that a sample of 30 people was taken. Analysis of the coefficient of variation is used to determine the magnitude of the risk and the Just and Pope model is used to identify risk factors. The results showed that (1) the risk of rice production in Lampulung Village, Pammana District, Wajo Regency was relatively large with a coefficient of variation of 0.524, meaning that for every ton of rice productivity that is expected, there is a productivity risk faced by a risk of 52.4 percent of total production which are expected; (2) The production factor that increases the risk of rice production is the seed factor. Variable land area, fertilizer, labor and pesticides are factors that can reduce or reduce the risk of rice production.